Determining of technological effectiveness of building systems by AHP method - Ginevičius, Romualdas; Podvezko, Valentinas; Andruškevičius, Algirdas (Technological and Economic Development of Economy, 2004)
The successful performance of construction enterprises as well as their competitiveness are largely determined by the construction technology and management methods used. In this respect two levels referring to a building or structure itself and to a construction enterprise as a whole should be distinguished. The technology of a building or structure embraces its construction system generally characterizing building materials, design solutions and load‐bearing structures and enclosures used in the construction of this particular building. The problem of selecting a general technological criterion for the whole construction enterprise arises. A construction enterprise fulfilling its annual program can simultaneously construct buildings and structures based on various construction systems, i.e. it can use various technologies. Searching for an integrated criterion to describe an enterprise as a whole three main issues including the variation of the applied technologies and their volumes and technological effectiveness should be taken into consideration. In the paper the problem of determining technological effectiveness of construction systems is considered. A method of pairwise comparison developed by T. Saaty was used to address this problem. The calculations were made for all thirteen technologies currently used in Lithuanian construction industry. Based on the suggested approach the weight of technological effectiveness was determined for each of them in the parts of one.Article in Lithuanian.Statybos sistemų technologiškumo nustatymas AHP metoduFirst Published Online: 21 Oct 2010